Excesso de água no solo sobre o desenvolvimento da grama Bermuda. - Nascimento Filho, Antonio Alves do (2013)
The drainage is an important stage in building a filed sports turf helping in the development of grass and in use by the users. For a drainage project information on the sensitivity of culture to stress by excess water will facilitate making decisions as to the design of the project. Assuming that the excess water affect the growth and development of the culture of grass and that the indices SEW30 and IDS are sensitive to the variables of development of the cultivation, the objective of this study was to identify the sensitivity of the culture of Bermuda grass to the excess of water based on the analysis of variables for crop development and stress treatments by excess water as referenced in the indices SEW30 and IDS. The experiment was conducted for three months with the Bermuda grass (Cynodon spp.) in the area of the Laboratory of hydraulic and irrigation of the Department of Agricultural Engineering of Federal University of Ceará (UFC). On the site were constructed tanks of masonry which measure 1.5 m in height, 2.0 m wide and 1.5 m in length, which allows you to control the level in the groundwater in different positions. The soil mix used the base of sand as per specifications of the United States Golf Association (USGA). The experimental design was completely randomized with five treatments and four replications. The treatments consisted of six elevations in the groundwater, varying the depths between 0.05 m and 0.20 m, and carried out monthly, with a duration of three days and the treatment without elevation of the groundwater. The variables used to test the treatment was root length, photosynthesis rate, dry weight of roots, rhizomes, stolons, culms and leaves and dry weight of clippings grass. In the variance analysis the treatments was compared by F test, considering a minimum level of significance was 5% probability. It was concluded that the values assigned to the variables analyzed showed decreases in their income with the increase in the stress level by excess water; The culture of bermudagrass was more sensitive to excess water in the first stage of development; and the photosynthetic rate at higher stress levels, decreases reaches approximately 2/3 of the value for the condition of no groundwater.